FOREIGN LANGUAGE INSTRUCTION: POSSIBLE APPLICATIONS OF THE SCHEMA THEORY - Shcherbukha, Roman (Collection of scientific papers «ΛΌГOΣ», 2025)
This paper discusses the schema theory, or the “schema reading theory”, which is a cognitive framework that describes the way individuals structure and process input. The schema theory was a response to the old behaviorist notion of the “bottom-up” approach, in which reading was conceived as a passive decoding process while meaning is extracted from the text alone .